Three years of the corruption eradication commission’s institutional reform: A narrative policy analysis (Integritas : Jurnal Antikorupsi, 2022)
Komisi Pemberantasan Korupsi (KPK) has been in a dramatic institutional transition since the enactment of the Second Amendment of the CEC Law in 2019, followed by a series of subsequent policies. The policy narrative presented by the government and the DPR as the policy-making actors is that the policy was carried out to strengthen the performance of the KPK. Meanwhile, counter-narratives emerged that said the opposite. This discourse took place intensively from 2019 to 2022, judging by the number of media reports. As a result of the narrative debate, based on several surveys, the KPK experienced a significant decline in the level of trust from the public. Using the Narrative Policy Analysis, this study poses the question: how does the government construct the KPK's institutional reform policy narrative? This research finds that the government policy narrative is built on distant belief systems but is not accompanied by adequate positive incentives, resulting in a prolonged polemic. In this study, it is suggested that the government conducts a comprehensive evaluation study of this policy, opens a space for open dialogue by involving counter-narrative actors, and conducts better policy advocacy.